Does Higher Government Spending Buy Better Results in Education and Health Care? - Verhoeven, Marijn (IMF Working Papers; Working Paper ;, 1999)
There is little empirical evidence to support the claim that public spending improves education and health indicators. This paper uses cross-sectional data for 50 developing and transition countries to show that expenditure allocations within the two social sectors improve both access to and attainment in schools and reduce mortality rates for infants and children. The size and efficiency of these allocations are important for promoting equity and furthering second-generation reforms.